2015
DOI: 10.1590/0004-282x20150112
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of non-functioning pituitary macroadenomas by the endoscopic endonasal approach in the elderly

Abstract: Over the past three decades, surgical series of elderly patients treated for pituitary adenomas have been published, all of which used the microscopic transsphenoidal or transcranial approach. The objective of this study was to retrospectively analyze the surgical results of our first 25 elderly patients with non-functioning pituitary macroadenoma (NFPM) operated by the endoscopic endonasal approach (EEA). Preoperative visual loss was found in 92.8% of the cases, and 70.8% experienced visual improvement follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
1
25
4
Order By: Relevance
“…Regarding procedural circumstances, increasing surgeon experience was positively associated with postoperative visual field deficit improvement in three studies (early groups: 75–86%; late groups: 90–100%) [ 5 , 8 , 9 ]. Furthermore, extend of resection was associated with poor visual field deficit outcomes in one study (p = 0.01), while three studies found no significant relation, both for visual acuity and visual field deficit outcomes [ 22 , 36 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Regarding procedural circumstances, increasing surgeon experience was positively associated with postoperative visual field deficit improvement in three studies (early groups: 75–86%; late groups: 90–100%) [ 5 , 8 , 9 ]. Furthermore, extend of resection was associated with poor visual field deficit outcomes in one study (p = 0.01), while three studies found no significant relation, both for visual acuity and visual field deficit outcomes [ 22 , 36 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 95%
“…Mean age per study ranged between 35.5 and 72.5 years (median: 50) and the percentage female patients ranged between 15 and 100% (median: 45%). Seven studies included only non-functioning pituitary adenoma patients [ 28 , 31 , 33 , 37 , 40 , 42 , 46 ]. Gross total resection grades were reported in 26 studies and ranged between 14 and 91% (median: 63.5%) (Table 1 ) [ 5 , 6 , 8 , 11 , 20 , 21 , 24 26 , 28 34 , 36 40 , 42 , 43 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to our results and those of Gondim et al, the analysis of Zhan et al showed equivalent complication rates in both groups (6.3% in the elderly group and 5.7% in the younger group; both groups had 7 cranial complications each [6 CSF leaks and 1 postoperative hematoma], and the older group had 3 cases of meningitis compared with 2 cases in the younger group; p = 0.85). Marenco et al 25 reported on 25 patients aged 65 years or older who underwent a total of 28 endoscopic procedures for nonfunctioning pituitary adenomas, but the authors did not provide any data for younger patients managed at their center. There was one perioperative death in their series (3.6% of 28 procedures), and complications were identified in 8 (32%) of the 25 patients.…”
Section: Discussionmentioning
confidence: 99%